A Randomized Controlled Trial of Opt-In Versus Opt-Out Enrollment Into a Diabetes Behavioral Intervention. Issue 3 (March 2018) - Aysola, Jaya; Tahirovic, Emin; Troxel, Andrea B.; Asch, David A.; Gangemi, Kelsey; Hodlofski, Amanda T.; Zhu, Jingsan; Volpp, Kevin
Purpose: To examine the effect of an opt-out default recruitment strategy compared to a conventional opt-in strategy on enrollment and adherence to a behavioral intervention for poorly controlled diabetic patients. Design: Randomized controlled trial. Setting: University of Pennsylvania primary care practices. Participants: Participants of this trial included those with (1) age 18 to 80 years; (2) diabetes diagnosis; and (3) a measured hemoglobin A1c (HbA1c) greater than 8% in the past 12 months. Intervention: We randomized eligible patients into opt-in and opt-out arms prior to enrollment. Those in the opt-out arm received a letter stating that they were enrolled into a diabetes research study with the option to opt out, and those in the opt-in arm received a standard recruitment letter. Measures: Main end points include enrollment rate, defined as the proportion of participants who attended the baseline visit, and adherence to daily glycemic monitoring. Analysis: We powered our study to detect a 20% difference in adherence to device usage between arms and account for a 10% attrition rate. Results: Of the 569 eligible participants who received a recruitment letter, 496 were randomized to the opt-in arm and 73 to the opt-out arm. Enrollment rates were 38% in the opt-out arm and 13% in the opt-in arm ( P < .001). Conclusions: Opt-out defaults, where clinically appropriate, could be a useful approach for increasing the generalizability of low-risk trials testing behavioral interventions in clinical settings.